Objections to Coercive Neurocorrectives for Criminal Offenders –Why Offenders' Human Rights Should Fundamentally Come First. Issue 1 (2nd January 2019) - Kirchmair, Lando
Abstract : "Committing a crime might render one morally liable to certain forms of medical intervention", claims Thomas Douglas, who stated in this context that "compulsory uses of medical correctives could in principle be justified." This article engages critically with his and other arguments on the use of coercive neurocorrectives for criminal offenders. First, the rehabilitation assumption that includes—for coercive neurocorrectives to work as an alternative to incarceration—that rehabilitation is the "only goal" of criminal punishment is criticized. Additionally this article engages with the theoretical difficulty of solely rehabilitative approaches, and discusses why it is unfortunate to design neurocorrectives so as to be particularly harmful in order to imagine administering them as being a punishment. Second, until we know more about specific neurocorrectives, we are well advised not to undermine the most important objection against coercive neurocorrectives, namely offenders' human rights. This article argues that the use of coercive neurocorrectives would particularly violate Article 3 of the European Convention on Human Rights which guarantees as an absolute right that "[n]o one shall be subjected to torture or to inhuman or degrading treatment or punishment", and finally holds that a still weak human right to mental integrity and self-determination should fundamentally come first.